PERANCANGAN LIGHT NOVEL SITTI NURBAYA DENGAN ILUSTRASI CAT AIR - Livia Wongso; Yana Erlyana (Universitas Bunda Mulia, 2020)
The design of this thesis aims to attract the reading interest of the Indonesian millennial generation to Indonesian old literature with light novel, The title is Sitti Nurbaya, adapted from the work of Marah Rusli with a similar title. It tells about Sitti Nurbaya's classic love story with forced marriage problems and other values in it.The research method used is a qualitative descriptive approach by collecting data from observations, literature studies and interviews.In this study, the authors obtained the results of a questionnaire distributed to 100 respondents who argued that the old Indonesian literature would be more interesting if added with illustrations because being able to build a new world of imagination created by stories and illustrations, unfortunately still rarely found illustrated novel books that lift old Indonesian literary works so that the old Indonesian literary works lacked the attention of the millennial generation. In this questionnaire, the author found that the genre of books that are of interest to the millennial generation is romance.To make this light novel take more time and effort starting from data collection, design process to production process. This also needs many attention to each design and illustration rule in order to attract readers. Through this design, it is expected to increase the appreciation of the millennial generation for Indonesia's old literary works.